2004
DOI: 10.1111/j.1439-0434.2004.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent Oospore Germination of Phytophthora cactorum in the Presence of Susceptible Host Plant

Abstract: Oospores of Phytophthora cactorum were produced in cleared V-8 broth supplemented with 30 mg/l b-sitosterol in the dark at 20-22°C for 2-3 months. Environmental conditions during oospore formation or maturation such as light, low temperature and also ageing could not compensate the light requirement for oospore germination. Dark grown oospores did not infect hypocotyl of susceptible safflower seedlings, an indicator plant for the pathogen, if they were not photoactivated 3-15 days or longer prior to infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Continuous light also inhibited oospore formation of the homothallic Phytophthora heveae (Brasier 1969) and a majority of other Phytophthora spp. previously tested (Banihashemi 2004;Harnish 1965;Yu et al 1981). Yu et al (1981) attributed this to inhibition to reduction of hormone production by light in heterothallic species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Continuous light also inhibited oospore formation of the homothallic Phytophthora heveae (Brasier 1969) and a majority of other Phytophthora spp. previously tested (Banihashemi 2004;Harnish 1965;Yu et al 1981). Yu et al (1981) attributed this to inhibition to reduction of hormone production by light in heterothallic species.…”
Section: Discussionmentioning
confidence: 94%
“…require light for oospore germination. Banihashemi (2004) noted that Phytophthora cactorum needs a minimum exposure to light for photoactivation of mature oospores. Chang & Shu (1988) observed that the homothallic species, P. cactorum and P. heveae did not germinate in the dark after 3 d. However, Jimenez & Lockwood (1982) and Sneh et al (1981) observed that Phytophthora megasperma f.sp.…”
Section: Discussionmentioning
confidence: 98%
“…Observation by Banihashemi (2004) proved that P. cactorum needed dark conditions during the formation and maturation of oospores. The germination would then occur if incubated under continuous fluorescent illumination, but would not occur without the exposure to light.…”
Section: Discussionmentioning
confidence: 99%
“…Germinating oospores formed germ tubes that would develop into hyphae and mycelia or sporangia which would in turn form zoospores. According to Banihashemi (2004), oospore germination is determined by the level of maturity of oospores as the internal factor, and an external factor such as exposure to light, whose duration depended on the species of Phytophthora.…”
Section: Discussionmentioning
confidence: 99%